1984
DOI: 10.1152/ajpgi.1984.246.3.g286
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic polypeptide inhibits exocrine pancreatic responses to six stimulants

Abstract: We determined the effects of three different doses of pancreatic polypeptide (50, 200, and 800 pmol X kg-1 X h-1) on pancreatic responses to graded doses of intravenous secretin, caerulein, and bethanechol and intraduodenal HCl, L-phenylalanine, and sodium oleate in dogs. The two lowest doses of pancreatic polypeptide (PP), which produced blood levels lower than measured after a meal, significantly inhibited the pancreatic responses to secretin, caerulein, HCl, and L-phenylalanine; the highest dose of PP inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
2

Year Published

1987
1987
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 0 publications
4
10
2
Order By: Relevance
“…In both the latter report (Ballesta et al, 1990) and the present study, the differences in the pancreatic response to food (in terms of volume and bicarbonate output) between the animals fed the olive or sunflower oil diets may be associated with the great effectiveness of oleic acid (the major fatty acid in olive oil) in stimulating the release of pancreatic polypeptide -PP - (Fink et al, 1983) and peptide YY -PYY - (Pappas et al, 1985), two peptides whose inhibitory action on exocrine pancreatic secretion is well known (Beglinger et al, 1984b;Lluis et al, 1987). Furthermore, our results suggest the existence of a direct relation between the amount of oleic acid in a diet consumed for a long period of time and the plasma concentration of both inhibitory peptides.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In both the latter report (Ballesta et al, 1990) and the present study, the differences in the pancreatic response to food (in terms of volume and bicarbonate output) between the animals fed the olive or sunflower oil diets may be associated with the great effectiveness of oleic acid (the major fatty acid in olive oil) in stimulating the release of pancreatic polypeptide -PP - (Fink et al, 1983) and peptide YY -PYY - (Pappas et al, 1985), two peptides whose inhibitory action on exocrine pancreatic secretion is well known (Beglinger et al, 1984b;Lluis et al, 1987). Furthermore, our results suggest the existence of a direct relation between the amount of oleic acid in a diet consumed for a long period of time and the plasma concentration of both inhibitory peptides.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, our results suggest the existence of a direct relation between the amount of oleic acid in a diet consumed for a long period of time and the plasma concentration of both inhibitory peptides. These were able to inhibit the pancreatic secretion stimulated by secretin (Beglinger et al, 1984b;Lluis et al, 1987), cholecystokinin (CCK) (Lluis et al, 1987) or both (Hosotani et al, 1989;Brodish et al, 1993). PYY also inhibits the release of CCK (Lluis et al, 1988;Hosotani et al, 1989), which, in turn, has been reported to potentiate the action of secretin on the fluid and bicarbonate secretion (You et al, 1983;Beglinger et al, 1984a;Chang & Lotti, 1986;Cantor et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Schmidt et al [16] reported the presence of an atropine-sensitive inhibitory mechanism and that PP might be a mediator of the inhibition. It has been demonstrated that PP has an inhibitory effect on exocrine pancreatic secretion [21,22], It can be ex plained by an inhibitory and atropine-sensi tive hormone such as PP so that the secre tory responses of water and bicarbonate se cretion to bombesin were enhanced by atro pine in the present study.…”
Section: Discussionsupporting
confidence: 51%
“…It is possible that pancreatic polypeptide, which inhibits pancreatic secretion [10] and is in fluenced by adrenergic agents [11], mediates the inhibi tory effects of terbutaline. However, this possibility is not proven.…”
Section: Discussionmentioning
confidence: 99%